A posteriori error analysis of an augmented mixed method for the Navier–Stokes equations with nonlinear viscosity. (November 2016) - Gatica, Gabriel N.; Ruiz-Baier, Ricardo; Tierra, Giordano
Abstract: In this work we develop the a posteriori error analysis of an augmented mixed finite element method for the 2D and 3D versions of the Navier–Stokes equations when the viscosity depends nonlinearly on the module of the velocity gradient. Two different reliable and efficient residual-based a posteriori error estimators for this problem on arbitrary (convex or non-convex) polygonal and polyhedral regions are derived. Our analysis of reliability of the proposed estimators draws mainly upon the global inf–sup condition satisfied by a suitable linearisation of the continuous formulation, an application of Helmholtz decomposition, and the local approximation properties of the Raviart–Thomas and Clément interpolation operators. In addition, differently from previous approaches for augmented mixed formulations, the boundedness of the Clément operator plays now an interesting role in the reliability estimate. On the other hand, inverse and discrete inequalities, and the localisation technique based on triangle-bubble and edge-bubble functions are utilised to show their efficiency. Finally, several numerical results are provided to illustrate the good performance of the augmented mixed method, to confirm the aforementioned properties of the a posteriori error estimators, and to show the behaviour of the associated adaptive algorithm.